Criminal Law Violations and Their Correlations Against Christian Ethics - Ferdy Sambo (Riviera Publishing, 2025)
This study aims to determine and find violations of criminal law and its correlation with Christian ethics. Violations of criminal law and its correlation with Christian ethics in the context of the Bible require repentance from the perpetrators of the crime. This type of research is a qualitative post-positivist research. The research method used is a qualitative post-positivist research method with a descriptive approach. Data collection used is library books and literature, surveys, interviews that are appropriate as references. Subject of Research Violations of criminal law and its correlation with Christian ethics. Object of Research Violations of Criminal Law and its Correlation with Christian Ethics. The results of the study found that violations of criminal law have a positive correlation with Christian ethics.